Tabagismo em pessoas com tuberculose: características sociodemográficas, clínicas, diagnósticas e de acompanhamento - Tonin, Edvaldo (2021)
Tuberculosis, a disease caused by Mycobacterium tuberculosis, more common in its pulmonary form, is an ancient disease that is still present and highly incident today. Socioeconomic, demographic, behavioral conditions and even the culture of a population can influence predisposition, incidence and treatments for the disease. In this sense, it is known that one of the aggravating factors to tuberculosis, its treatment and its outcome is related to smoking. Objective: To analyze the use of tobacco in people with tuberculosis according to sociodemographic, clinical, diagnostic and follow-up profile. Method: Descriptive study, carried out in a sectional way with a quantitative approach, carried out from secondary data of incident cases of tuberculosis diagnosed between 2010 and 2018 and obtained from the Epidemiological Surveillance sector in the city of Foz do Iguaçu-PR. The group of smokers and nonsmokers was compared according to sociodemographic, clinical and treatment variables, using Fisher's exact test, Chi-square and standardized residue analysis at a significance level of 5%. Results: A significant association was identified between smoking in people with TB and the male, aged 40 to 60 years old, elementary school, deprivation of liberty and home lessness. In clinical characteristics, an association was found with the pulmonary form of the disease, alcoholism and drug use. In the diagnostic characteristics, there was evidence of an association between smoking and relapse/reentry after quitting, chest X-ray suggestive of TB, positive sputum culture and drug resistance. Regarding the monitoring of patients, there was a statistically significant association with treatment abandonment, drug- resistant TB and treatment duration of two, four and five months. Conclusion: It is evident that the prevalence of smoking among TB cases is related to men, older age groups, low education level, people deprived of their liberty, people on the streets and people with behaviors harmful to their health, such aso ther psychoactive substances such as alcohol and illicit drugs. Research shows that smoking is directly linked to more severe radiological images of pulmonary TB, which is prevalent among smokers, who are more likely to relapse and re-enter treatment after quitting, as well as the drug resistance and difficulty in maintain in regularity of treatment, showing the need for dialogue between the TB Control Program and the National Tobacco Control Policy.